Globalization and the American IT Worker. - Matloff, Norman (Communications of the ACM, 2004)
The article examines the effect of globalization of information technology (IT) on U.S. programmers and its economic development. In spite of the recent attention given to offshoring, labor importation today is the bigger problem for the country's IT workers. A 2004 report commissioned by the Information Technology Association of America, a major industry-lobbying group, found that only 104,000 U.S. IT jobs were lost during 2000-2003 due to offshoring. There is no question that having the work done on-site is more productive than shipping it overseas. Offshoring often results in longer completion times and lost market opportunities due to delays. Good software development requires constant interaction among developers and managers being able to walk down the hall for spur-of-the moment face-to-face conversations. Another major problem with offshoring is that the Indian business model involves staffing projects with young, inexperienced programmers in order to minimize costs. This has adverse effects on quality. Thus, labor importation must be addressed, not only for its direct effect but also because it plays a central role in offshoring; most offshoring software projects include a key onshore component staffed by H-1Bs and L-1s in the country.